Language Research Methodology (Theory And Practice) - murdiono, murdiono (Jurnal Pendidikan Indonesia, 2023)
Understanding "Research Methodology in Language" is crucial as it provides a critical foundation for the exploration, analysis, and interpretation of language phenomena. Through appropriate research methods, we can delve into the structures of language, communication patterns, and changes in meaning with the necessary depth. The importance of language research methodology lies in its ability to provide systematic guidance for researchers in designing and conducting research relevant to their specific goals. Language research methods also play a vital role in the development of language theories, bridging empirical understanding with broader conceptual frameworks. It supports innovation in research approaches and enriches our understanding of language diversity as well as changes in social, cultural, and technological contexts. In the educational context, a profound understanding of language research methodology provides the basis for designing effective and relevant teaching strategies. This in-depth understanding also supports efforts in language and cultural preservation, offering detailed insights into how language functions in specific societal contexts. Overall, understanding "Research Methodology in Language" is essential for advancing linguistic knowledge, providing deep insights into language phenomena, and informing various practical aspects, from education to cultural preservation.